Effect of entomopathogenic fungi on the cattle tick Boophilus microplus (Acari: Ixodida): use of pathogenicity activators - RAYMOND-C., KARIM; ROJAS-B., FABIOLA; BENAVIDES-O., EFRAÍN; COTES, ALBA MARINA; VILLAMIZAR, LAURA; RONDEROS-J., VANIA; GARCÍA-M., PAOLA (Revista Colombiana de Entomología, 2004)
In arthropod-pathogen systems, the value of using pathogenicity activators to improve growth, sporulation  capacity and  adherence  of entomopathogenic  fungi to  arthropods  has  been  demonstrated. The  objective of the  work was  to  study the  biocontrol activity of two  isolates of Metarhizium anisopliae (Mt019  and   Mt020)  on  the  tick Boophilus  microplus,  by  examining the  use  of pathogenicity activators used  during the  fungal culture phase.  A completely randomized design was used.  testing three treatments applied by aspersion:  culture  on  traditional  agar (EM),  media  plus unspecific  pathogenicity  activator  (S) and  the  same  media  with a tick-specific activator  (SA).  The  experimental  unit was a group of ten engorged ticks  (five  replicates)  and  fungal  concentration  was constant at  108  conidia  ml-1. Analysis of the  results was based  on  the  parameters IEC (Conversion  Efficiency lndex)  and  ER (Reproductive  Efficacy),  indicators of reproductive  capacity of the  tick and  PCIEC  (Percentage  Control  of IEC),  and  PCONER  (Percentage  Control ER),  associated  with  fungal  efficacy.  There was  an  effect  of pathogenicity  activators  on  the  two  fungi evaluated;  the  IEC value was lower  (p<  0,01)  in  groups with activator.  In  the  case of ER. values  were  lower for groups  with  activator  but  not  statistically  significant.  Control  levels  (PCIEC  and  PCONER)  were significantly higher (p<  O.O 1)  in the  two  treatments with activator for both parameters in the two  fungal isolates.  It  was  concluded that the  use  of pathogenicity  activators  during the  culture  phase  is  a process that  ensures  a better  biocontrol  effect  of fungi  on  ticks.